Titanium implant alters the effect of zoledronic acid on the behaviour of endothelial cells. (12th May 2021) - Yu, Yi; Liang, Chaoan; Xu, Ruogu; Wang, Tianlu; Deng, Feilong; Yu, Xiaolin
Abstract: Objectives: To evaluate the effect of zoledronic acid (ZA) on human umbilical vein endothelial cells (HUVECs) attached to different surfaces. Materials and Methods: A total of three groups were evaluated in this study: sandblasting and acid etching (SLA) + HUVECs; mechanically polished (MP) + HUVECs; and plastic cell culture plates + HUVECs. Scanning electron microscopy, energy‐dispersive X‐ray spectroscopy, surface roughness and water contact angle were tested for titanium surface characterisation. ZA was added at different concentrations (0, 1, 10, 50 and 100 μM). Cell adhesion, proliferation, viability, apoptosis and gene expression were evaluated. Results: Mechanically polished and SLA surfaces showed negative effects on cell adhesion and proliferation and promoted cell apoptosis with 100 μM ZA ( p  < .05). The highest expression of intercellular adhesion molecule‐1 (ICAM‐1) and angiopoietin‐1 was found on SLA surfaces ( p  < .01). The lowest expression of platelet‐endothelial cell adhesion molecule‐1 and ICAM‐1 was found on MP surfaces ( p  < .05). A significant decrease in von Willebrand factor was detected on MP and SLA surfaces ( p  < .001). Conclusions: Zoledronic acid has an anti‐angiogenic effect on HUVECs attached to titanium implants, while the SLA surface might stimulate HUVECs to express angiogenic and adhesive factor genes despite ZA treatment.